Let's sit down and talk: The art of breaking bad news - Ghellai, Ali; Elhafi, Kafia; Ghellai, Maram; Ghellai, Mamoon (Ibnosina Journal of Medicine and Biomedical Sciences, 2021)
Physicians often are uncomfortable when communicating bad or difficult news. In the absence of much effective training, many doctors find that breaking bad news is one of the most difﬁcult, demanding, and stressful tasks. A significantly negative relationship can form between the patient and their medical staff if poor communication is used. Most patients want the truth, but how bad news is delivered can substantially influence a patient's emotions, satisfaction, subsequent psychological adjustments, and attitudes toward treatment. Moreover, values in certain cultures can become barriers that can limit or pressure a physician in ethically approaching the patient. Disclosing bad news is a complex communicational task that requires time, compassion, and empathy. Although breaking bad news will never be easy, communicating well is a skill that can be learned. The SPIKES protocol provides a simple and easily learnable strategy for communicating bad news.
Keywords: Breaking bad news; communication skills; empathy; SPIKES protocol